2010
DOI: 10.1002/pds.2078
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced physician adherence to antibiotic use guidelines through increased availability of guidelines at the time of drug ordering in hospital setting

Abstract: In this study, the increased availability of antibiotic guidelines at the time of drug ordering, combined with a periodical reinforcement educational round, was associated with an enhanced physician adherence to these guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Implementation of e-prescribing systems in hospitals presents a unique opportunity to improve the quality of antimicrobial prescribing and to facilitate AMS. [5][6][7][8][9][10] Evidence for the benefits of AMS functionality within e-prescribing systems comes from published research studies demonstrating positive impact on outcomes including increased guideline adherence 11,12 and effective initial therapy 13 or reductions in antimicrobial prescribing, 14,15 resistance, 16,17 dosing errors, 8 length of hospital or ICU stay 14,18 and mortality. 12,13,19 However, many of these information systems were created on a small scale in individual hospitals or groups of institutions and few reports cover the full potential range of software features that enable AMS.…”
mentioning
confidence: 99%
“…Implementation of e-prescribing systems in hospitals presents a unique opportunity to improve the quality of antimicrobial prescribing and to facilitate AMS. [5][6][7][8][9][10] Evidence for the benefits of AMS functionality within e-prescribing systems comes from published research studies demonstrating positive impact on outcomes including increased guideline adherence 11,12 and effective initial therapy 13 or reductions in antimicrobial prescribing, 14,15 resistance, 16,17 dosing errors, 8 length of hospital or ICU stay 14,18 and mortality. 12,13,19 However, many of these information systems were created on a small scale in individual hospitals or groups of institutions and few reports cover the full potential range of software features that enable AMS.…”
mentioning
confidence: 99%
“…In the period using paper-based guidelines, only 15.43% of patients were prescribed antibiotic categories and 32.9% of patients were administrated according to time course recommended by the guidelines during antibiotic prophylaxis of surgical operations. It was reported that the most predictable impact was achieved when the guidelines are made available through computer-based reminders that are integrated into the clinician's workflow and provide therapeutic information to prescribers ‘just-in-time’ to influence the decision at the time of clinical decision [13], [14], [15], [26]. Shojania [27] developed a system in which the CDC recommendations for vancomycin use were presented online to the surgeon at the time of drug ordering on a hospital's computer-based order entry system, which found that surgeons who were randomly assigned to receive the intervention wrote 32% fewer orders for vancomycin compared with control group.…”
Section: Discussionmentioning
confidence: 99%
“…So the key point to prevent SSIs is to improve the dependence on the guidelines for the prevention of SSIs. In addition, some studies have reported that making guidelines or decision supports can supply therapeutic information to prescribers ‘just-in-time’ to influence the decision at the time of clinical decision, so that surgeon is likely to apply it [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…18 They concluded that the presentation of antibiotic guidelines at the time of drug ordering via the CPOE in combination with scheduled educational reinforcement enhanced physician adherence to specific aspects of guidelines (choice, dose, duration), although overall, there was no significant difference in the proportion of nonadherent antibiotic orders in the postintervention period. They suspect physician beliefs regarding guidelines may play a role in this finding.…”
Section: Computerized Physician Order Entrymentioning
confidence: 96%